Sensitivity of Elmidae (Insecta: Coleoptera) to habitat disturbance and physicochemical water quality in lotic environments of the Colombian Andes - González Córdoba, Marcela (2020)
Introduction: Riffle beetles are aquatic organisms frequently associated with well-oxygenated clean running water; however, some genera of Elmidae can also be found in moderately polluted streams proving their tolerance to certain degree of habitat degradation. Objective: In order to determine the contamination sensitivity and tolerance of each genus and the main factors that influence the presence and composition of Elmidae in Colombia, Methods: 60 locations between 450 and 4000 masl were sampled in six localities of Colombia, mainly in the Andean Region. Collection was carried out with D and Surber nets. Physico-chemical, bacteriological and environmental quality information was recorded. With these data, Canonycal Correspondence Analysis and descriptions of occurrence intervals for each genus were made. Results: Twenty-two genera were found in the streams evaluated; which represents 85% of known national richness. The most important factors influencing the presence and composition of Elmidae were oxygen saturation, sediment deposition, suspended solids, epifaunal substrate availability and geographic location. Conclusions: Results are useful for classifying elmids according to their sensibility to changes in environmental conditions and habitat degradation, which is a first step to incorporate Elmidae in water quality biotic indexes.